Anxiety and Test Form: The Differences of Test Anxiety Levels in Terms of Test Form - Lussy Dwiutami Wahyuni; Rezza Citraini; Bijak Aditia Hutomo; Gumgum Gumelar (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2021)
Education is one of the most important aspects of human life. In the education file, examination is an important part to evaluate the progress of the students. The students need to fulfill the test parameters and indicators in order to move to the higher level of class or higher degree. The common feeling while students feel anxious in facing the test is called test anxiety. There are several factors that affect test anxiety, and one of the most common sources is the test form. This study aimed to determine the differences in test anxiety levels in students in terms of multiple-choice and matchmaking tests. The population of this study was 142 students of the Faculty of Psychology Education that registered in 2018. The design of this study was a quasi-experimental research with two-group pretest-posttest design. The instrument used in this study was the Reaction to Test scale by Irwin G. Sarason. The results showed that the multiple-choice test anxiety level was higher than the matching test, although the difference was small. The multiple-choice test anxiety level was (M = 2.17) and matchmaking (M = 2.07).